Quince Duncan : writing Afro-Costa Rican and Caribbean identity - Mosby, Dorothy E., 1970- (University of Alabama Press, 2014)
Quince Duncan is a comprehensive study of the published short stories and novels of Costa Rica's first novelist of African descent and one of the nation's most esteemed contemporary writers. The grandson of Jamaican and Barbadian immigrants to Limón, Quince Duncan (b. 1940) incorporates personal memories into stories about first generation Afro-West Indian immigrants and their descendants in Costa Rica. Duncan's novels, short stories, recompilations of oral literature, and essays intimately convey the challenges of Afro-West Indian contract laborers and the st.